Surveillance of vibrio parahaemolyticus in shellfish purchased from selected retailers in Selangor, Malaysia - Tan, Malcolm Turk Hsern (2015)
The aims of this study were to optimize the multiplex polymerase chain reaction (mPCR) assay for the detection of V. parahaemolyticus and the respective pathogenic strains (tdh+ and/or trh+), and to compare with the loop-mediated isothermal amplification (LAMP) assay. These assays were not limited to detection only, and likewise coupled with the most probable number (MPN) to quantitate the bacterium in various shellfish samples obtained from wet markets and hypermarkets. The surveillance data were later adopted into a stochastic microbial risk assessment (MRA) model to evaluate the public health risk. In addition to these, a kitchen simulation was conducted to provide cross-contamination and decontamination data. A total of 232 samples comprising of bloody clams, surf clams and shrimps were randomly purchased from the wet markets and hypermarkets in Selangor. 229 (98.7%) of the samples were positive for V. parahaemolyticus with counts ranging from 30 to >110, 000 MPN/g. Positive samples for tdh+ V. parahaemolyticus were obtained in 77 out of 232 (33.1%) samples ranging from 30 to >110, 000 MPN/g. Meanwhile, positive samples for trh+ were identified in 16 out of 232 (6.9%) samples examined ranging from 30 to 9,600 MPN/g. In addition, we found that LAMP was rather more robust and sensitive compared to the multiplex PCR. Bloody clam was selectively picked for a thorough MRA as the pathogenic strains of V. parahaemolyticus were prevalent in this sample. The study framework was established based on the currently available experimental and survey data in combination with the @RISK software to simulate the uncertainties based on the Monte Carlo simulation. The estimated risk was valued as 1.04E-4/daily serving/person. This translates to an estimate of 250 to 197,000 cases yearly. The simulation of the handling of bloody clams in domestic kitchens was designed to imitate real events in domestic kitchens as much as possible to give a realistic quantitative data on how V. parahaemolyticus could cross-contaminate to other readyto-eat (RTE) foods (eg, lettuce). It was found that 20.40 ±13.78% of the total V. parahaemolyticus population from the bloody clams were transferred to the hands and kitchen utensils through primary cross-contamination, and the cut lettuce had an average of 7432.5 MPN/g of V. parahaemolyticus. The attempted cleanings reduced the transferred population by 97.63 ± 3.43% (water) and 96.00 ± 5.03% (cloth), and the cut lettuce had an average of 9.27 MPN/g of V. parahaemolyticus. Likewise, the bacterial transfer was minimal for secondary cross-contamination, which recorded 46.2 MPN/g (from contaminated water to lettuce) and 0.75 MPN/g (from contaminated plate to lettuce). In conclusions, there is an immediate need for further investigation to look into the widespread of V. parahaemolyticus in Malaysia. Continued research, risk assessment and surveillance on the behaviour and characteristics of V. parahaemolyticus is very important in order to control, prevent and reduce the emerging problems caused by this interesting bacterium.